A Preliminary Study on Educating Hospitalized Geriatric Vascular Patients on the Use of Movement-Induced Computer Games to Improve Exercise Attitudes. Issue 2 (3rd April 2017) - Thomas, David W.; Wolfe, Robert
ABSTRACT: A critical challenge confronted by vascular care professionals is developing an effective strategy to motivate patients, who are typically older, to adopt new healthy behaviors that include exercise. Teaching new behaviors is further complicated by a short length of stay (typically less than five days) associated with acute rehabilitation care. This preliminary study, investigated whether a brief (1–2 session) orientation to movement-induced computer games, that were also intrinsically satisfying, effected attitudes toward exercise among vascular patients. Ten vascular patients on a hospital rehabilitation unit were assessed based on their exercise attitudes before and after receiving a movement-induced computer game orientation session using the Outcomes Expectations of Exercise scale (OEE). Post-test scores were also compared with perceived exertion as measured by the BORG-CR10. Statistical significance was found between pre and post OEE scores ( p < .001), although there was a weak correlation between OEE and BORG-CR10 scores. The findings suggest that the activity professional can play an important role in teaching intrinsically rewarding movement-induced computer games to vascular patients, which in turn, may have a positive influence on exercise attitudes.